2016
DOI: 10.18561/2179-5746/biotaamazonia.v6n1p31-39
|View full text |Cite
|
Sign up to set email alerts
|

Gradiente Latitudinal da Beta Diversidade da Fauna Acompanhante das Pescarias Industriais de Camarões Marinhos da Costa Norte do Brasil

Abstract: RESUMO.A pesca industrial de camarões no Norte do Brasil é praticada por embarcações equipadas com redes de arrasto que apresentam baixa seletividade, capturando elevada quantidade de organismos não pertencentes à espécie-alvo, gerando uma grande biomassa de fauna acompanhante. Este trabalho objetivou realizar o levantamento da composição e distribuição da ictiofauna acompanhante proveniente de pescarias industriais de camarão-rosa, no período de maio de 2010 a junho de 2011. Foram monitorados sete embarques, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
7

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 16 publications
1
13
0
7
Order By: Relevance
“…2A). Complementary data were obtained through a literature search (Pinheiro, Frédou, 2004;Oliveira et al, 2004;Maia et al, 2016).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…2A). Complementary data were obtained through a literature search (Pinheiro, Frédou, 2004;Oliveira et al, 2004;Maia et al, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…Different fishery techniques are used to target determined species, although all types of industrial fishery operation result in the harvesting of bycatch, that is, species captured unintentionally (Eayrs, 2007;Davies et al, 2009). The amount and diversity of this bycatch may vary significantly among different fishery operation (Clucas, 1997), and among fishing grounds and seasons (Paiva et al, 2009;Maia et al, 2016). Outrigger trawling, in particular, is known for its reduced selectivity and high proportion of incidental catch (Perez, Pezzuto, 1998;Diamond et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While C. similis had not previously been recorded from the northern Brazilian state of Pará, our examination of material obtained from CEPNOR indicated that the fish identified by Maia et al (2016) as pescada-negra is, in fact, Cynoscion similis, given that this species is the only Atlantic sciaenid that presents dark pigmentation. In the same way, quite possibly the species went undetected in other inventory studies of local industrial fisheries, recorded as Cynoscion sp.…”
Section: Discussionmentioning
confidence: 53%
“…Batrachoides surinamensis is reported in literature as ranging in Brazil from Amapá to Bahia states and it was recently recorded in Amapá (Maia et al 2016), Pará (Ferreira et al 2011), Maranhão (Piorski & Nunes 2010), Piauí (Mai et al 2012), Ceará (Osório et al 2011), Paraíba (Oliveira 2011), Pernambuco (Pinto et al 2015), and Alagoas (Paiva et al 2013). In the conservation status may not represent historical declines.…”
Section: Notes On Geographic Distributionmentioning
confidence: 99%